Analisis Implementasi dan Keberlanjutan Bisnis Doughbi di Kota Palembang - Maretha, Chelsy; Megawati, Megawati (Universitas Multi Data Palembang, 2026)
This study aims to analyze the implementation and sustainability of Doughbi, a culinary business producing purple sweet potato donuts in Palembang City. The research method used is descriptive with quantitative and qualitative approaches through marketing mix analysis, financial performance analysis, and business sustainability assessment. The results indicate that Doughbi can be well implemented and has good sustainability potential.